2022
DOI: 10.3390/ijms23169279
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the Ability of Witch Hazel (Hamamelis virginiana L.) Bark Extract to Impair Keratinocyte Inflammatory Cascade Typical of Atopic Eczema

Abstract: Hamamelis virginiana L. bark extract is a traditional remedy for skin affections, including atopic dermatitis/eczema (AD). Hamamelis preparations contain tannins, including hamamelitannin (HT), although their pharmacological role in AD is still unknown. This study aimed to study the rational for its topical use by considering the impact of crucial biomarkers on AD pathogenesis. A standardized extract (HVE) (0.5–125 μg/mL) was compared to hamamelitannin (HT), its main compound (0.5–5 μg/mL), in a model of human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 54 publications
0
6
0
1
Order By: Relevance
“…Similarly, HAM was also reported to be an anticancer, anti-inflammatory, antioxidant agent as well as a quorum sensing inhibitor as established in earlier studies in the literature [25][26][27][28][29][30][31]. It was observed in a study that HAM possessed anti-colon cancer activities as it showed lower IC 50 values against various colorectal cell lines in MTT assay.…”
Section: Therapeutic Potential Of Ginnalin a And Hammentioning
confidence: 74%
See 1 more Smart Citation
“…Similarly, HAM was also reported to be an anticancer, anti-inflammatory, antioxidant agent as well as a quorum sensing inhibitor as established in earlier studies in the literature [25][26][27][28][29][30][31]. It was observed in a study that HAM possessed anti-colon cancer activities as it showed lower IC 50 values against various colorectal cell lines in MTT assay.…”
Section: Therapeutic Potential Of Ginnalin a And Hammentioning
confidence: 74%
“…In another set of experiments, HAM was found to be active against chemokine (C-C motif) ligand 26 (CCL26), K10, and cell proliferation and hence hindered the interleukin-4 (IL-4) inflammatory pathway. Thus, it was found to be effective against the keratinocyte inflammatory cascade [ 28 ]. In yet another set of experiments, the murine skin fibroblasts were exposed to ultraviolet (UV)-B (UVB) radiation.…”
Section: Therapeutic Potential Of Ginnalin a And Hammentioning
confidence: 99%
“…Recently, our group of researchers attributed an anti-inflammatory activity to a polar extract from witch hazel bark and twigs (0.5–125 μg/mL) in HaCaT cells challenged with TNF-α and IL-4 [ 52 , 84 ]. The extract was characterized by the presence of oligomeric proanthocyanidins (0.29%) and hamamelitannin (0.30%) as the main compounds.…”
Section: Resultsmentioning
confidence: 99%
“…Der Extrakt hemmte sowohl die Freisetzung von Mediatoren, die an der Haut Autoimmungeschehen vermitteln (IL-6 und IL-17C), als auch solche, die allergische Reaktionen auslösen (TSLP, IL-6, CCL26 und MMP-9). Zudem wirkte er der proliferativen Wirkung von IL-4 entgegen und regenerierte K10, einen Marker für die Hautdifferenzierung, was die positive Wirkung von Hamamelis bei Juckreiz und Beeinträchtigung der Hautbarriere erklärt [23].…”
Section: Zauberstrauch Zaubernuss (Hamamelis Virginiana)unclassified